A Meta-Analysis of the Relationships Between Emotional Intelligence and Employee Outcomes - Doǧru, Çaǧlar (Frontiers in Psychology, 2022)
Emotional intelligence is an ever-growing concept in the literature since 1990s due to its important outcomes for employees. This study is a psychometric meta-analysis examining the links with emotional intelligence and organizational commitment, organizational citizenship behavior, job satisfaction, job performance and job stress of employees. In this meta-analysis, carefully selected studies on emotional intelligence since the birth of the concept in 1990, and also the studies examining its outcomes are included. Conducting this analysis, emotional intelligence was taken in three forms consistent with previous meta-analyses. These are ability, self-report and mixed emotional intelligence. This meta-analysis is an attempt to contribute to the literature by analyzing the relationships between emotional intelligence and selected employee outcomes in a wide range of time, beginning from 1990. In this context, the three forms of emotional intelligence were separately analyzed to examine the relationships with employee outcomes included in the study by taking the selected researches into consideration. According to the results, both emotional intelligence and its three streams turned out to be positively related to organizational commitment, organizational citizenship behavior, job satisfaction and job performance, whereas negatively related to job stress.